Image Encryption System Based On Chaotic System And DNA Computing - Li, Yunyi; Xu, Jiangfeng (2021 2nd International Conference on Computer Engineering and Intelligent Control (ICCEIC), 2021)
The misuse and arbitrary tampering of digital images by third parties pose a threat to the security and privacy of human subjects, requiring the development of good encryption techniques to meet the security needs of digital images. In this paper, we focus on the image encryption algorithm based on the combination of hyper chaotic system and DNA operation, which divides the digital image into three two-dimensional matrices by R, G and B channels, encrypts the image in blocks, and the chaotic sequence generated by the chaotic system determines the DNA coding, decoding and operation of each image block in the encryption process. The number of chaotic systems in the algorithm is increased and the encryption process is optimized to address the problems of low key space and inability to resist cropping attacks. The simulation results show that the improved encryption algorithm can resist the exhaustive key attack, the correlation of adjacent elements of the encrypted image is greatly reduced, and the encrypted image is resistant to cropping.